Inscription on the wall of Our Lady of the Rosary Church - Mumbai Archive Project Team (Jio Institute, 2024)
Ownership and management of the Catholic churches began to diverge after the Portuguese gave the British control of the Bombay Islands. ‘Descendentes’ were the descendants of the Portuguese, while ‘naturalis,’ which included the Kolis, were the natives who had undergone conversion. The descendants refused to let the naturalis inside Gloria Church. The naturalis objected and urged the government to provide them land in Mazagon so they could construct their own church. Consequently, Our Lady of the Rosary Church was constructed on this land in 1794, as indicated by the inscription on the wall.